ANALISIS RENCANA PENDISTRIBUSIAN ROKOK GUNA MEMINIMALKAN BIAYA TRANSPORTASI PADA PT. SURYA MADISTRINDO CABANG KISARAN - M Idris (Universitas Dharmawangsa, 2018)
Distribution is closely related to transportation where without transportation the distribution cannot run smoothly as expected. Every company has various obstacles in distributing goods, one of theobstacles is the amount of costs that must be spent for the distribution of goods.The purpose of thisresearch is to find out the activities of cigarette distribution applied by the company and help thecompany in minimizing transportation costs in the process of distributing cigarettes from one placeto another as well as analyzing the plans that will be done company for distribution runs as expected.The technique of data analysis is descriptive and comparative analysis.Based on hypotersis used bywriter in this case, hence in analysis chapter show that hypothesis accepted because at distributionprocess can minimize transportation cost from Rp. 168,000,000 to Rp. 84.000.000 there is a decreasein cost of Rp. 84.000.000 which is very profitable for the company without reducing the largecapacity of goods distributed. The results obtained and at the same time become the conclusion thatthe influence of distribution to the cost is very significant because if the distribution is done withoutthe plan will increase the cost, so before doing the distribution it is better to create a strategic planto avoid cost increment